BUSINESS FEASIBILITY ANALYSIS ON FRESH FILLET PRODUCTS GOLDBAND SNAPPER (Pristimoides multidens) PT. MATSYARAJA ARNAWA STAMBHAPURA KUPANG, EAST NUSA TENGGARA - Rahardian, Mydan Amlang; Suseno, Suseno; Lailatussifa, Rr. Radipta; Nugraha, Breva Rizqi D. (Universitas Mataram, 2025)
Indonesia, as the largest archipelagic country in the world with a vast water area, has great potential in the fisheries industry. One of the leading products that has the potential to compete in the international market is fish fillets. PT. Matsyaraja Arnawa Stambhapura, which has been engaged in the processing of fishery products since 2017, has exported fresh fillet and frozen fillet products to various countries such as Australia, Singapore, Canada, and America. To ensure the sustainability of its business, a business feasibility study is needed that includes market, technical, human resource, environmental, and financial aspects. This study aims to evaluate investment potential and business feasibility to support optimal business decision making. The purpose of this study is to determine the business feasibility of the company PT. Matsyaraja Arnawa Stambhapura. This research was conducted on February 24 - May 09, 2025. This research was conducted by means of a survey with an internship method with quantitative data sources to analyze financial aspects through certain predetermined indicators. Business analysis obtained at the company PT. Matsyaraja Arnawa Stambhapura is a net profit of IDR 389,539,726, with BEP Unit 100 units, BEP price of IDR 2,035,965, Payback Period of 1.76 months and B/C Ratio of 1.91. So this business is feasible to be established.